Tissue Expression Of The 6-Pyruvoyi Tetrahydropterin Synthase Gene In Adult Zebrafish,Danio Rerio. - Kuah, Meng Kiat; Chan, Woon Khiong; Tengku Muhammad, Tengku Sifzizul; Chong, Alexander (2004)
Teleost is one of the poikilotherms that can display different kind of colours on their body. This is due to the presence of different types of chromatophores, a group of pigment containing cells that is distributed in the epidermal layer of skin and scales.